Ptolemaic political activities on the west coast of Hellenistic Asia Minor had a significant impact on the local spread of the Isiac cults: A spatial network analysis - Glomb, Tomáš; Mertel, Adam; Pospíšil, Zdeněk; Chalupa, Aleš (PloS one, 2020)
During the reign of the first Ptolemaic kings in Egypt, mainly in the 3rd and 2nd centuries BCE, the Egyptian cults related to the divine couple of Isis and Sarapis (i.e. the Isiac cults) spread successfully from Egypt to ports and coastal cities of the ancient Mediterranean. The discussion on the topic of the factors involved in the process of the early spread of these cults outside Egypt is still open and, so far, the research in this area has been conducted mainly by using established historiographical methods. However, these methods are limited when dealing with the interplay among different variables involved in complex historical processes. This article aims to overcome these limits by using a quantitative spatial network analysis. The results of our previous published research, which focused on a quantitative evaluation of the impact of individual factors on the early spread of the Isiac cults across the ancient Aegean Islands, suggest that the process was promoted by military and commercial activities of the Ptolemaic dynasty, and that the Ptolemaic military operations were the most influential factor. Following these results, this article focuses on the early spread of the Isiac cults on the west coast of Hellenistic Asia Minor, i.e. the region which the Ptolemies attempted to control in the 3rd and 2nd centuries BCE. The statistically significant results presented in this article support the hypothesis that the Ptolemaic political engagement in Asia Minor had a positive impact on the early spread of the Isiac cults. The results also suggest that the activities of the Seleucid dynasty, a political rival of the Ptolemies, in the area of interest could have constituted an immunological factor limiting the spread of the Isiac cults further to the eastern parts of Asia Minor.
Keywords: Spatial Analysis; Politics; Asie; Transportation; archeologie; Archaeology; lidé; politika; Asia; Egypt, Ancient; doprava; prostorová analýza; starověký Egypt; dějiny starověku; History, Ancient; Humans